Edible Coating Innovation Based on Taro Stem (Colocasia esculenta L.) and Used Waste Oil to Prevent Food Loss - Vania Evangelista Evelina Susanto; Putu Udayani Pradnya Maheswari; Made Chantika Artameivia Pradnya Putri; Ni Made Margiani (Research in Chemical Engineering, 2024)
Food loss, especially in perishable items like fruits, is a critical global issue. This study introduces “ECOLA,” an innovative edible coating made from taro stem starch (Colocasia esculenta L.) and natural glycerol derived from spent cooking oil. The research aimed to evaluate ECOLA’s chemical properties (solubility and water vapor transmission rate), physical properties (density and tensile strength), and organoleptic characteristics. The coating was applied to extend the shelf life of fruits such as tomatoes, avocados, and mangoes. The optimal formulation, consisting of taro stem starch (2.5 g), CMC (2.5 g), glycerol (2.5 g), and water (175 g), demonstrated remarkable properties, including high tensile strength (47.834 MPa), balanced density (1.190 g/cm³), and strong consumer approval. The coating significantly reduced water vapor transmission and extended fruit freshness by up to 14 days compared to untreated samples. ECOLA showcases tremendous potential for reducing food loss while promoting sustainability through the utilization of organic waste, such as spent cooking oil. By enhancing food preservation in an eco-friendly manner, ECOLA addresses critical challenges in food security and waste management. This study highlights ECOLA as a viable, sustainable, and environmentally friendly solution for the agricultural sector to mitigate food loss and achieve food security targets.